Solution of the partial derivative equation with nonlinear boundary conditions - Da, Hoang Van (Vietnam Journal of Mechanics, 1987)
In this paper, the asymptotic method has been used to construct the solution of the partial derivative equation with nonlinear conditions, describing vibration of the rectangular thin plate. It is shown that the physical nonlinearity of the boundary has influence on oscillational characteristics of systems.